Diversity of Capitalism in Central and Eastern Europe Dependent Economies and Monetary Regimes - Magnin, Eric.; Nenovsky, Nikolay (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book explores the hypothesis of the emergence of a 'dependent capitalism' in Central and Eastern Europe. In a first theoretical part, this book presents the main approaches that structure the field of comparative capitalism and then examines this model shaped by the inflow of foreign capital. In an original way, it proposes to integrate the form of the monetary regime into the dependent capitalism analysis and to extend it to Balkan countries. The monetary regime is seen as complementary to the other elements of the institutional configuration of dependent capitalism. In the second part, the authors adopt a historical and empirical perspective. First, they demonstrate how dependent capitalism has emerged in Central and Eastern Europe and the Baltic States over the last 30 years as part of the process of socio-economic transformation that began in 1990. The crisis of 2008 was an indicator of this dependence on Western capital. Secondly, they extend the analysis to the Balkan countries and show that dependence is even stronger for them, particularly in the monetary area, as evidenced by the implementation of currency boards or euroization phenomena. This book is of interest to academics and students, as well as to business and economic policy makers. Eric Magnin is Associate Professor of Economics at the University Paris City, France. Former Head of the Department of Economics, his research focuses on transition economies and comparative capitalism. Nikolay Nenovsky is Professor of Economics at the University of Picardie, France, and associated researcher at the National Research University Higher School of Economics and RUDN University in Moscow, Russia. He has published widely in the areas of currency boards and central banking, especially of post-communist countries. He has broad, practical experience as a researcher and later as a member of the Governing Council of the Bulgarian Central Bank and different EU institutions.
Chapter 1: Introduction -- Part I: Theoretical Foundations -- Chapter 2: Varieties or Diversity of Capitalism? -- Chapter 3: Dependent Capitalism -- Chapter 4: Dependent Monetary Regime -- Part II: Empirical And Historical Perspectives -- Chapter 5: Dependent Capitalism in Central and Eastern Europe -- Chapter 6: Dependent Monetary Regimes in Post-communist Balkan periphery : Currency Boards in Bulgaria and Bosnia and Herzegovina -- Chapter 7: Dependent Monetary Regimes in Post-communist Balkan periphery : Unilateral Euroization in Montenegro and Kosovo -- Part III: Conclusion -- Chapter 8: Concluding remarks. Dependent monetary regimes during the pandemics.
Keywords: International economic relations; Economics; Economic policy; Social policy; International Economics; Political Economy and Economic Systems; Socio-Economic Policy